A novel mutation in the SLC19A2 gene in a Turkish male with thiamine-responsive megaloblastic anemia syndrome - Odaman-Al, Işık; Gezdirici, Alper; Yıldız, Melek; Ersoy, Gizem; Aydoğan, Gönül; Şalcıoğlu, Zafer; Tahtakesen, Tuba Nur; Önal, Hasan; Küçükemre-Aydın, Banu (The Turkish Journal of Pediatrics, 2019)
Thiamine-responsive megaloblastic anemia (TRMA) is a very rare syndrome characterized by the triad of early onset megaloblastic anemia, sensorineural deafness and diabetes mellitus. Here we report, a 5-year-old boy who presented with transfusion dependent anemia and diabetes mellitus and was diagnosed with TRMA. Besides reporting a novel mutation of the causative gene SLC19A2, we wanted to emphasize this syndrome in the aspect of coexistence of insulin dependent diabetes, transfusion dependent anemia and thrombocytopenia.
Keywords: SLC19A2 mutation; diabetes mellitus; thiamine-responsive megaloblastic anemia; thrombocytopenia